Pleiotropic Effects of Sodium-Glucose Cotransporter-2 Inhibitors: Renoprotective Mechanisms beyond Glycemic Control - Tomoaki Takata (International Journal of Molecular Sciences, 2021)
Diabetes mellitus is a major cause of chronic kidney disease and end-stage renal disease. However, the management of chronic kidney disease, particularly diabetes, requires vast improvements. Recently, sodium-glucose cotransporter-2 (SGLT2) inhibitors, originally developed for the treatment of diabetes, have been shown to protect against kidney injury via glycemic control, as well as various other mechanisms, including blood pressure and hemodynamic regulation, protection from lipotoxicity, and uric acid control. As such, regulation of these mechanisms is recommended as an effective multidisciplinary approach for the treatment of diabetic patients with kidney disease. Thus, SGLT2 inhibitors are expected to become key drugs for treating diabetic kidney disease. This review summarizes the recent clinical evidence pertaining to SGLT2 inhibitors as well as the mechanisms underlying their renoprotective effects. Hence, the information contained herein will advance the current understanding regarding the pleiotropic effects of SGLT2 inhibitors, while promoting future research in the field.